Representasi Nilai Sosial Dan Budaya Dalam Novel Indonesia Sebagai Cermin Realitas Masyarakat Modern Kontemporer - Rastra Sewa Kottama (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to analyze the representation of social and cultural values in Indonesian novels as a reflection of contemporary modern society. The research employs a qualitative approach using a descriptive-interpretative method within the framework of literary sociology. The data are derived from purposively selected contemporary Indonesian novels and supported by relevant scholarly sources. Data collection techniques include intensive reading and textual documentation of social and cultural values represented in the narratives. The findings reveal that contemporary Indonesian novels represent social values such as social solidarity, class conflict, individualism, and power relations, as well as cultural values including local traditions, modernity, gender roles, and identity crises. These representations reflect the dynamics of social and cultural changes in modern Indonesian society. This study concludes that novels function not only as aesthetic works but also as media for social reflection and critical discourse on contemporary societal realities.